How Deep Are the Invisible Wounds? The Impact of Maternal Stress During Pregnancy on Adolescent Anxiety: A Cross-Sectional Study - Dessy Ekawati; Nurul Azmi Arfan; Esti Pratiwi Yosin; Endang Yuswatiningsih (NSC Nursing)
Background: Pregnancy-related stress can affect a child’s development for a long time, increasing the likelihood of teenage anxiety. High levels of stress hormone exposure during pregnancy may interfere with the development of the nervous system and stress reactions, making a person more susceptible to anxiety disorders. Objective: The purpose of this study is to determine the degree to which prenatal stress leads to teenage anxiety and to examine the association between maternal stress during pregnancy and teenage anxiety levels. Methods: A cross-sectional design was used, involving 143 mothers with adolescents aged 10–19 years, selected through purposive sampling. The Prenatal Distress Questionnaire (PDQ) was used to measure prenatal stress, while the Generalized Anxiety Disorder-7 (GAD-7) was used to measure anxiety in adolescents. The link between prenatal stress and teenage anxiety was examined using Spearman’s correlation, and the impact of prenatal stress on teenage anxiety was ascertained using ordinal regression. Results: Prenatal stress and teenage anxiety were significantly positively correlated, according to Spearman’s correlation test (r= 0.51; p < 0.0001). Ordinal regression analysis indicated that prenatal stress significantly influenced adolescent anxiety (Chi-Square = 27.9; p < 0.0001), explaining 45.6% of its variability (Nagelkerke R²= 0.46). Conclusion: Maternal stress during pregnancy showed a moderate, significant positive correlation with adolescent anxiety (r= 0.51; p < 0.0001), explaining 45.6% of the variance in anxiety levels. Strengthening psychosocial support for pregnant women and implementing early prenatal stress detection programs are essential strategies to reduce the risk of anxiety disorders in their children. These findings highlight the need for psychological support programs for pregnant women to reduce the risk of anxiety disorders in their children.